OCENIANIE KOMPETENCJI STUDENTÓW – PRZYSZŁYCH NAUCZYCIELI JĘZYKA OBCEGO PRZEZ NAUCZYCIELI – OPIEKUNÓW PRAKTYK, NA PRZYKŁADZIE JĘZYKA FRANCUSKIEGO - Monika Grabowska (Neofilolog, 2019)
The aim of this paper is to analyse how French teachers evaluate the didactic skills of students of the Institute of Romance Studies after their three-week teaching practice in a Polish middle or high school. We will be interested primarily in the descriptive evaluation written by the supervising school teachers, which affords an overview of the key competences of foreign language teachers in their own opinion (i.e. their personal theory of teaching) as well as of the terminology used to describe them and reflecting modern or more traditional conceptions of teaching. Our analysis will be carried out with reference to the competences highlighted in a self-evaluation tool, the European Portfolio for Students Teachers of Languages. Conclusions are drawn regarding not only the need to strengthen cooperation between the university and the school teachers to instil a reflective attitude, but also to strengthen the correlation between the tutors’ evaluation and the self-evaluation of the trainees – not only to develop their autonomy, but also for formative assessment of both the student and the teacher.